CONSTRUCTIVE LEADERSHIP IN REGIONAL GOVERNANCE: INSIGHTS FROM ASTA BRATA TEACHINGS IN GIANYAR DISTRICT - I Ketut Pasek Lanang Sadia; I Nengah Lestawi; I Wayan Wastawa (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
This article explores constructive leadership in the regional governance of Gianyar Regency, inspired by the Asta Brata teachings—eight Hindu leadership principles symbolizing cosmic powers such as the sun, moon, and wind. It examines how the Regent of Gianyar (2018–2023) embodied these values in public policy, citizen services, and participatory, sustainable development. A qualitative ethnographic approach was employed to explore the philosophical and social dimensions of Hindu leadership. Findings reveal that applying Asta Brata fosters visionary, ethical, and welfare-oriented leadership. Core values such as justice (Yama), generosity (Kuwera), and spiritual motivation (Agni) are evident in infrastructure development, education, health services, and community empowerment. The study concludes that Asta Brata remains relevant in modern governance as a philosophical and ethical foundation, particularly in the context of decentralized regional leadership.